Model Matematika Tingkat Partisipasi Masyarakat dalam Pemilu di Indonesia - Patrik Wahyu Yubelian; Noorma Yulia Megawati (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2023)
General elections in Indonesia are a means of people's sovereignty for the election of president and vice president as well as legislative officials which are carried out directly, publicly, freely, confidentially, honestly, and fairly every 5 years. One indicator of election success is the level of public participation. In every general election, there must be white groups or called abstainers who consciously do not exercise their right to vote for their own reasons. This group of abstainers can influence other people not to exercise their right to vote. In this paper, we discussed about the mathematical model of the level of public political participation in general elections. In this mathematical model, the abstainer-free equilibrium point, the abstainer equilibrium point, and the basic reproduction number will be determined. The analysis shows that for Ro<1, free abstainer equilibrium point is asymptotically stable and for R0>1, the abstainer equilibrium point is exists and asymptotically stable. Finally, a numerical simulation will be carried out to verify the results of the theoretical analysis. The numerical simulation shows that the condition of the abstainer-free population can be achieved but it takes a very long time.